Morbihan disease complicated by dermatosis neglecta: An unique presentation. (16th February 2017) - Eber, Ariel E.; Mlacker, Stephanie; Verne, Sebastian; Griffith, Robert; Ledon, Jennifer; Perper, Marina; Nouri, Keyvan; Cho‐Vega, Jeong Hee
Abstract : Morbihan disease, also referred to as solid facial edema, or rosacea lymphedema, is a rare disorder that involves chronic erythema and solid edema of the cheeks, eyelids, forehead and glabella and may arise as a complication of acne vulgaris or rosacea. Of note, it may be the only initial presenting symptom of these associated diseases. Few cases have been described in the literature, as its first description by Robert Degos in 1957. The condition is characterized by its chronicity, a typical clinical appearance and the lack of specific histopathologic or laboratory findings. The condition may wax and wane but typically does not resolve without treatment. Many cases of this condition tend to be recalcitrant to therapy, with topical and oral antibiotics regimens commonly used for rosacea generally being ineffective. The disease may easily go undiagnosed, as it mimics other more common skin conditions. We present a case of originally undiagnosed Morbihan disease mistaken for an atypical allergic rash, resistant to treatment, and complicated by dermatosis neglecta.